2021
DOI: 10.3390/gels7040223
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Electrospun Polyvinyl Alcohol/Nanocellulose Composite Film and Evaluation of Its Biomedical Performance

Abstract: Using polyvinyl alcohol (PVA) and nanocellulose (NC) as raw materials, PVA/NC nanofiber membranes were prepared by electrospinning. The hydrogen bonding, crystalline properties and microscopic appearance of PVA/NC membranes with different NC contents were characterized. The mechanical properties, liquid absorption and cytotoxicity of the nanofiber membrane were evaluated. The results show that the free hydroxyl group of the PVA/NC nanofiber membranes have a maximum value of 9% at a mass fraction of 6% NC. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Natural biopolymers such as polysaccharides and their derivatives (alginates, chitosan, cellulose, curdlan, etc. ), proteins (collagen, gelatine, fibrin, keratin) and proteoglycans are used for wound dressings preparation due to their biodegradability, biocompatibility, haemostatic activity, and non-toxicity [ 8 , 9 , 10 ]. We chose curdlan because it is a natural polysaccharide with a higher potential in biomaterials fabrication.…”
Section: Introductionmentioning
confidence: 99%
“…Natural biopolymers such as polysaccharides and their derivatives (alginates, chitosan, cellulose, curdlan, etc. ), proteins (collagen, gelatine, fibrin, keratin) and proteoglycans are used for wound dressings preparation due to their biodegradability, biocompatibility, haemostatic activity, and non-toxicity [ 8 , 9 , 10 ]. We chose curdlan because it is a natural polysaccharide with a higher potential in biomaterials fabrication.…”
Section: Introductionmentioning
confidence: 99%
“…This may be due to the addition of CS and SECS leading to hydrogen bonding interactions with PVA, resulting in a decrease in the orderliness of its crystal structure. 24 Fourier-transform infrared spectroscopy (FTIR) was employed to assess the cross-linking status of the components in the hydrogel samples. The intensity of the peaks linked to hydroxyl groups around 3300 cm −1 in the SECS-PVA hydrogel was significantly higher compared to that in other samples (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This may be due to the addition of CS and SECS leading to hydrogen bonding interactions with PVA, resulting in a decrease in the orderliness of its crystal structure. 24…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have shown that adding nanocellulose particles can result in a crystalline structure. The PVA matrix and the cellulose nanowhiskers form a strong hydrogen bond interaction [ 51 , 52 ].…”
Section: Resultsmentioning
confidence: 99%